Capturing and testing perceptual-cognitive expertise: A comparison of stationary and movement response methods - Roca, A.; Williams, A. M.; Ford, P. R. (Behavior Research Methods, 2014)
Numerous methods have been used to study expertise and performance. In the present article, we compare the cognitive thought processes of skilled soccer players when responding to film-based simulations of defensive situations involving two different experimental conditions. Participants either remained stationary in a seated position (n = 10) or were allowed to move (n = 10) in response to life-size film sequences of 11 versus 11 open-play soccer situations viewed from a player`s perspective. Response accuracy and retrospective verbal reports of thinking were collected across the two task conditions. In the movement-based response group, participants generated a greater number of verbal report statements, including a higher proportion of evaluation, prediction, and action planning statements, than did participants in the stationary group. Findings suggest that the processing strategies employed during performance differ depending on the nature of the response required of participants. Implications for behavioral methods and experimental design are discussed.